Energy efficiency of waste gasification plants in the national municipal waste management system - Arkadiusz Primus; Dagmara Buntner; Czesława Rosik-Dulewska; Tadeusz Chmielniak (Archives of Environmental Protection)
To achieve high levels of municipal waste recovery through a system employing mechanical-biological waste processing technologies, effective management of the over-sieve fraction of mixed municipal waste (preRDF) is crucial. This preRDF cannot be landfilled due to its combustion heat exceeding 6 MJ/kg. Therefore, thermal treatment of waste and subsequent energy recovery become pivotal in the national waste management system, particularly amidst energy crises and fluctuating energy prices. Waste-derived energy can serve as a valuable renewable energy source. To ascertain the true efficiency of the plant in terms of energy, environmental impact, and economics, it is vital to organize the concepts of energy efficiency for thermal waste treatment plants. The energy efficiency of a waste gasification plant should be comprehensively assessed from three standpoints: energy efficiency of thermal waste treatment (i.e., energy efficiency index), energy efficiency of recovering chemical energy contained in waste (actual energy efficiency of the plant), and the efficiency of renewable energy production. A thermal waste processing plant qualifies as a renewable energy source, when it generates electricity and heat from the biodegradable fraction of waste. This article endeavours to determine the potential contribution of chemical energy from the biodegradable waste fraction, relying on preRDF fraction test results..